The Immediate Effect of Trigger Point Injection With Local Anesthetic Affects the Subsequent Course of Pain in Myofascial Pain Syndrome in Patients With Incurable Cancer by Setting Expectations as a Mediator - Hasuo, Hideaki; Matsuoka, Hiromichi; Matsuda, Yoshinobu; Fukunaga, Mikihiko (Frontiers in Psychiatry, 2021)
A trigger point injection (TPI) with local anesthetic in myofascial pain syndrome (MPS) often has the immediate effect of a decrease in pain. It is unknown whether the immediate effect of a decrease in pain affects the subsequent course of pain. It is also unknown whether expectations of a decrease in pain mediate such effects. We aimed to clarify how the effect of a decrease in pain immediately after TPI with local anesthetic affected the subsequent course of pain, and whether it increased expectations of a decrease in pain. This was a prospective, single-center, observational clinical trial. Patients with incurable cancer who visited the palliative care department and received TPI with local anesthetic for MPS were prospectively examined. We evaluated whether the immediate effect of a TPI with local anesthetic affects the subsequent course of pain in MPS by setting expectations as a mediator, using path analysis. From 2018 to 2020, 205 patients with incurable cancer received TPI for MPS. Of these, 58.1% of patients reported an immediate effect of decreased pain. Compared with the non-immediate effect group, the immediate effect group had higher expectations of a decrease in pain, and the higher expectation was maintained at 7 days (p < .001). The percentage of patients with pain reduction at 7 days after TPI was 88.2% in the immediate effect group and 39.5% in the non-immediate effect group (p < .001). The immediate effect of decreased pain had the greatest influence on pain reduction at 7 days, both directly (β = 0.194) and indirectly through increased expectations (β = 0.293), as revealed by path analysis. The effect of a decrease in pain immediately after TPI with local anesthetic affected the subsequent course of MPS pain in patients with incurable cancer by setting expectations as a mediator. There were limitations to the discussion of these findings because this was an observational study.